Book Review: Classic Hikes of the World - Sharma, Sunil (Nepal Tourism and Development Review, 2013)
DOI: http://dx.doi.org/10.3126/ntdr.v1i1.7375 Nepal Tourism and Development Review Vol.1(1) 2011 124-126